Bargaining over Babies: Theory, Evidence, and Policy Implications - Matthias Doepke; Fabian Kindermann (Institute for the Study of Labor (IZA), 2016)
It takes a woman and a man to make a baby. This fact suggests that for a birth to take place, the parents should first agree on wanting a child. Using newly available data on fertility preferences and outcomes, we show that indeed, babies are likely to arrive only if both parents desire one, and there are many couples who disagree on having babies. We then build a bargaining model of fertility choice and match the model to data from a set of European countries with very low fertility rates. The distribution of the burden of child care between mothers and fathers turns out to be a key determinant of fertility. A policy that lowers the child care burden specifically on mothers can be more than twice as effective at increasing the fertility rate compared to a general child subsidy.
Keywords: J13; 330; fertility; bargaining; child care